Mewujudkan Cita Hukum Yang Efektif: Suatu Pandangan Teoritis - Kamaruddin Kamaruddin (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2006)
This study aims to analyze the concept of an effective legal ideal from the perspective of legal theory. The legal ideal is a normative foundation in the formation and application of law that reflects the values of justice, certainty, and expediency. This study uses a qualitative method with a literature review approach, examining various legal theories and their relevance in building a responsive and effective legal system. The results show that the effectiveness of the legal ideal is influenced by normative and institutional factors, as well as public legal awareness. An ideal law must not only be written in regulations, but must also be applied fairly and in accordance with social needs. This study emphasizes that realizing an effective legal ideal requires a balance between clear regulations, strong law enforcement, and active community participation in the legal system.